Extreme Instability in Electoral System Changes: The Turkish Case - Cop, Mehmet Burak (My University, 2011)
This article examines the extremely volatile character of electoral system changes that took place in Turkey from the end of the Second World War up until the end of the 1990s. Motives that drove these changes were either related to intentions to prevent the undesirable repetition of the past circumstances, or to political actors’ short-term goals. Some of these changes seem to have reached their objectives while some others have not. The volatility in electoral institutions’ design was also strongly associated with the fluctuations Turkey experienced in terms of democratic consolidation. In this respect, the Turkish case may offer a variety of useful empirical material for the prospective designers of new institutions in a number of former communist countries that are likely to experience further stages of democratic transition/consolidation in the years ahead.
Keywords: Türkiye; Siyaset ve Yönetim; Demokrasi; Turkey; Politics and Government; Democracy